2022
DOI: 10.3389/fcvm.2022.811657
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Determinants of Visit-to-Visit Lipid Variability: Genome-Wide Association Study in Statin-Naïve Korean Population

Abstract: Background and AimThere is a growing evidence that fluctuation in lipid profiles is important in cardiovascular outcomes. We aimed to identify single nucleotide polymorphism (SNP) variants associated with low-density lipoprotein-cholesterol (LDL-C) and high-density lipoprotein-cholesterol (HDL-C) variability in statin-naïve Korean subjects and evaluate their associations with coronary atherosclerosis.MethodsIn statin-naïve subjects from Gene-Environment of Interaction and phenotype cohort, we performed genome-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…We, for the first time, identified significant association of PXDNL variants rs16916207 and rs11985241 with APAC ( Table 4 and Supplementary Table 3 ). PXDNL is an associated gene between the obese individuals and never-overweight controls [ 14 ], and associated with high-density lipoprotein-cholesterol variability [ 37 ], suggesting that PXDNL could be related to the weight. Our genotype-phenotype correlation analysis showed that the APAC subjects carrying the risk alleles of rs11985241 and rs16916207 variants had significantly lower weight than those carrying the protective allele ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We, for the first time, identified significant association of PXDNL variants rs16916207 and rs11985241 with APAC ( Table 4 and Supplementary Table 3 ). PXDNL is an associated gene between the obese individuals and never-overweight controls [ 14 ], and associated with high-density lipoprotein-cholesterol variability [ 37 ], suggesting that PXDNL could be related to the weight. Our genotype-phenotype correlation analysis showed that the APAC subjects carrying the risk alleles of rs11985241 and rs16916207 variants had significantly lower weight than those carrying the protective allele ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants may contribute the link of lipid variability and coronary artery stenosis. In a recent study of statin-naive Koreans, some single nucleotide polymorphisms (SNPs) related to LDL-cholesterol variability or HDL-cholesterol variability were found to be associated with advanced coronary artery stenosis ( 16 ). It is also unknown whether the same mechanism causes higher variability of LDL-cholesterol, HDL-cholesterol, and triglycerides, indicating that variability of one lipid measurement did not correlate well with the variability of the others in the Treating to New Targets (TNT) trial ( 8 ).…”
Section: Discussionmentioning
confidence: 99%